GPs' suspicion of child abuse: how does it arise and what is the follow-up? - Erik Stolper; Jan Paul Verdenius; Geert-Jan Dinant; Margje van de Wiel (Taylor & Francis Group, 2020)
Background: Child abuse is widespread, occurs in all cultures and communities, remains undiscovered in 90% of cases and has serious long-term effects. Physicians generally underidentify and underreport child abuse. To understand this low reporting rate and how the suspicion of child abuse arises, we examined GPs' experiences. Research questions: How does the suspicion of child abuse arise in GPs' diagnostic reasoning? How do they act upon their suspicion and which barriers do they encounter in their management? Methods: Twenty-six GPs participated in four focus groups. We used purposive sampling to include GPs with different levels of experience. We performed a thematic content analysis. Results: Suspicion of child abuse arose from common triggers and a gut feeling that 'something is wrong here'. GPs acted upon their suspicion by gathering more data, through history taking and physical examination. They often found it difficult to decide whether a child was abused, because parents, despite good intentions, may simply lack parenting skills and have different values. Clear signs of sexual abuse and physical violence were institutionally reported by GPs, whereas in less clear-cut cases they followed them up and built a supporting network of professionals around the family. Conclusions: A low child abuse reporting rate by GPs to CACRC does not mean a low detection rate. In trying to improve a child's situation, GPs make use of patients' trust in their doctor by involving other professionals. Awareness of the role of gut feelings in developing a suspicion may increase early detection and preventive actions.Key points Physicians generally underidentify and underreport child abuse. Suspicion of child abuse arose from common triggers and a gut feeling that 'something is wrong here'. GPs acted upon their suspicion by gathering more data, through history taking and physical examination. GPs found it difficult to decide whether a child was abused, because parents, despite good intentions, may lack parenting skills.